Laboratory Diagnosis and Monitoring of Diabetes Mellitus. Issue 5 (4th January 2016) - Emancipator, Kenneth
Abstract : The American Diabetes Association emphasizes fasting plasma glucose (FPG) levels, rather than the oral glucose tolerance test (OGTT), to diagnose diabetes mellitus. The diagnostic cutoff for FPG is 126 mg/dL (7.0 mmol/L). A 2-hour plasma glucose level of 200 mg/dL (11.1 mmol/L) or more during an OGTT or a random plasma glucose level of 200 mg/dL (11.1 mmol/L) or more also is diagnostic of diabetes. The 100-g, 3-hour OGTT remains the "gold standard" for gestational diabetes mellitus (GDM). Two of 4 samples exceeding cutoffs (fasting, ≥105 mg/dL [5.8 mmol/L]; 1 hour, ≥190 mg/dL [10.5 mmol/L]; 2 hours, ≥165 mg/dL [9.2 mmol/L]; 3 hours, ≥145 mg/dL [8.0 mmol/L]) indicate GDM. An effective GDM screening test is plasma glucose 1 hour after a 50-g oral glucose load. Tight control, which requires self-monitoring of blood glucose, reduces microvascular complications for patients with type 1 or type 2 diabetes. Patients with well-controlled diabetes have glycohemoglobin concentrations of 7 %A1c (0.07 A1c /A) or less. Microalbuminuria indicates early, reversible, diabetic nephropathy. The random urine albumin-creatinine ratio is a convenient effective screening test. Albumin-creatinine ratios in the 0.03 to 0.30 (g/g) range indicate microalbuminuria.